2022
DOI: 10.1007/s11211-022-00398-z
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Gender Equality: A Systematic Review of Interventions

Abstract: More than four decades have passed since the United Nation’s Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) was adopted. Now is an opportune time to consider whether the interventions seeking to realise CEDAW’s aspirations have brought us closer to achieving gender equality. This systematic review aimed to identify and synthesise evidence for the effectiveness of social justice, cognitive, or behaviour-change interventions that sought to reduce gender inequality, gender bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Education and awareness-raising strategies, also predominantly had only partial beneficial effects. 28 The Economic and Social Council (ECOSOC 1997/2), defined gender mainstreaming as "a strategy for making women's as well as men's concerns and experiences an integral dimension of the design, implementation, monitoring and evaluation of policies and programmes in all political, economic and societal spheres so that women and men benefit equally, and inequality is not perpetrated. Initiative; research funding agency initiatives and tackling challenges around sexual harassment.…”
Section: Discussionmentioning
confidence: 99%
“…Education and awareness-raising strategies, also predominantly had only partial beneficial effects. 28 The Economic and Social Council (ECOSOC 1997/2), defined gender mainstreaming as "a strategy for making women's as well as men's concerns and experiences an integral dimension of the design, implementation, monitoring and evaluation of policies and programmes in all political, economic and societal spheres so that women and men benefit equally, and inequality is not perpetrated. Initiative; research funding agency initiatives and tackling challenges around sexual harassment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has found that the effectiveness of most interventions to end and prevent CRSV around the world is far from evident (Nordås and Cohen, 2021). For example, educational and awareness-raising preventive measures, which are clearly incentivized by the CCC, have only partial effects in regard to reducing sexism and gender inequality in society (Guthridge et al, 2022). Furthermore, the CCC also makes a strong emphasis on reducing impunity as a key preventive measure.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions encompass a broad spectrum of activities, treatments, programs, or initiatives designed to tackle specific issues, achieve defined outcomes, or influence particular variables [22]. Considering the specific barriers that motherhood imposes on women's career advancement, gender-and motherhood-sensitive interventions may offer important opportunities for leveling the playing field if they aim to reduce gender inequality and transform social conditions by addressing structural issues such as biases and stereotypes [7].…”
Section: The Need For Interventions To Address the Underrepresentatio...mentioning
confidence: 99%